Contributions of the international plant science community to the fight against human infectious diseases – part 1: epidemic and pandemic diseases. Issue 10 (19th July 2021) - Lobato Gómez, Maria; Huang, Xin; Alvarez, Derry; He, Wenshu; Baysal, Can; Zhu, Changfu; Armario‐Najera, Victoria; Blanco Perera, Amaya; Cerda Bennasser, Pedro; Saba‐Mayoral, Andera; Sobrino‐Mengual, Guillermo; Vargheese, Ashwin; et al.
Summary: Infectious diseases, also known as transmissible or communicable diseases, are caused by pathogens or parasites that spread in communities by direct contact with infected individuals or contaminated materials, through droplets and aerosols, or via vectors such as insects. Such diseases cause ˜17% of all human deaths and their management and control places an immense burden on healthcare systems worldwide. Traditional approaches for the prevention and control of infectious diseases include vaccination programmes, hygiene measures and drugs that suppress the pathogen, treat the disease symptoms or attenuate aggressive reactions of the host immune system. The provision of vaccines and biologic drugs such as antibodies is hampered by the high cost and limited scalability of traditional manufacturing platforms based on microbial and animal cells, particularly in developing countries where infectious diseases are prevalent and poorly controlled. Molecular farming, which uses plants for protein expression, is a promising strategy to address the drawbacks of current manufacturing platforms. In this review article, we consider the potential of molecular farming to address healthcare demands for the most prevalent and important epidemic and pandemic diseases, focussing on recent outbreaks of high‐mortality coronavirus infections and diseases that disproportionately affect the developing world.